Governance and Corruption in Arm's Length Public Institutions: Two Belgian Case Studies. (4th March 2023) - De Jaeger, Alexander
Abstract: Recent major corruption cases in Belgium center around arm's length public institutions. Is there is a specific relationship between governance mechanisms and corruption in such institutions that weakens their accountability? To answer this question, the principal-agent framework was applied to two Belgian case studies. This study supports the hypothesis that New Public Management reforms, such as decentralization and diminishing state intervention have rendered the character of corruption more sophisticated. The study also shows how failures in governance mechanisms led to corruption, but more importantly how corruption, both by the agent and by the principal, contributed to that failure in the first place. Consociationalism and partitocracy, characteristic of the Belgian political system, are important contextual elements that help explain this relationship between governance and corruption, and suggest that the observed corruption is probably not exceptional. To better prevent corruption in arm's length public institutions, the focus should be on strengthening the independence and expertise of members in governance structures, ensuring the independence of the audit and regulatory functions, and investing the limited means available to fight corruption in the principal-agent relationship rather than in the agent-client relationship.